Biomass corridor synthesis for malaysia green energy supply chain - Ng, Wendy; Ng, R.; Lam, H.; Kamal, M.; Ng, E.; Ng, D. (The Italian Association of Chemical Engineering, 2012)
The urban cities of Malaysia are enclosed by greenery, mainly oil palm plantation which it covers 4.98 Mha of the land area of the country. Due to the huge volume of oil palm availability, palm biomass appears to be one of the key concerns to the country. Space and technologies are needed to allocate the resulting palm biomass, which its volume is directly proportional to the amount of palm fresh fruit bunches (FFB) being processed. Due to the characteristics of biomass being low density, porous and low calorific value, the biomass may be integrated with other source of useful material, say waste industrial oil, to boost up its efficiency for incineration while symbiotically tackling the waste oil disposal difficulty. The Malaysian government has set a target on the biomass generated renewable energy. However, the realisation of the energy target is challenging. The crop aging and promotion of replanting policy by the government may reduce the availability of biomass, which threatens the accomplishment of the energy target. The adapted biomass with higher energy value may be able to tackle the mentioned threat, enhancing the energy security of the country. In this work, a biomass energy supply plan is proposed and a simplified supply network design is presented.